Are kids who have obese adoptive parents at increased risk for obesity compared with kids without obese adoptive parents?. Issue 7 (July 2018) - Giruzzi, Nicholas R.; Payette, Nicole; Larson, Paul; Haugh, Amy J.; Wilson, Stephen A.
Abstract : EVIDENCE‐BASED ANSWER : Data are limited concerning the development of obesity that utilizes adoption to control for genetic influences. Available evidence suggests both genetics and the environment contribute to obesity (no SOR given).